Penyuluhan dan Pemeriksaan Leptospirosis terhadap Petani di Nagari Alahan Panjang Kabupaten Solok - Elizabeth Bahar; Netti Suharti; Roslaili Rasyid; Andani Eka Putra; Linosefa Linosefa; Muhammad Reza; Arni Amir (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
Leptospirosis is an infectious disease caused by Leptospira interogans (L interogans). The urine of rats is a carrier of L interrogans bacteria that pollutes stagnant water such as flooding both in rice fields and fields. Bacteria enter through the mucosa and sores or blisters when in contact with the polluted water. The mortality rate due to leptospirosis in Indonesia is reported to reach 2.5 - 16.45%, because it is a tropical country with quite high rainfall followed by flooding. Nagari Alahan Panjang Solok Regency is located at an altitude of 1400 - 1600 meters above sea level (masl) with rainfall of 2600 mm which is a vast agricultural area and the community is 90% farmers. Based on the problem above, the Department of Microbiology and Biology, Faculty of Medicine, Andalas University has held community service in Nagari Alahan Panjang, Solok Regency, for farmers, because farmers are at risk of being infected by Leptospira. The counseling method uses a power point slide and poster about leptospira followed by blood tests using the Standard Q rapid test for Leptospira IGM / IgG. About 48 farmers carried alcohol swabs at the tips of their fingers to take blood samples with fingersticks. As much as 10 ul of blood add 1 drop of standard buffer solution Q rapid test Leptospira IgM / IgG put in the rapid test tool well while stirring and wait 5 minutes. Positive results appear in the red line in the IgM / IgG area according to the control indicated on the rapid test tool. The conclusion that counseling can increase the knowledge of farmers to prevent leptospirosis with the discovery of 6.25% of farmers suspected of leptospirosis.